2016
DOI: 10.1136/bjophthalmol-2015-307798
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of video clips and interactive games to improve vision in children with amblyopia using the I-BiT system

Abstract: BackgroundTraditional treatment of amblyopia involves either wearing a patch or atropine penalisation of the better eye. A new treatment is being developed on the basis of virtual reality technology allowing either DVD footage or computer games which present a common background to both eyes and the foreground, containing the imagery of interest, only to the amblyopic eye.MethodsA randomised control trial was performed on patients with amblyopia aged 4–8 years with three arms. All three arms had dichoptic stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 22 publications
2
71
1
4
Order By: Relevance
“…Dichoptic training is normally based on the use of polarized glasses, whereas for binocular therapy the use of red-green glasses is required. With both techniques, binocular fusion training is performed using stimuli with some common parts and disparate elements for each eye individually [17,18]. Specifically, active visual therapy based on perceptual learning, dichoptic stimulation, and binocular training with anaglyph glasses is an interesting new area of research that can complement and optimize conventional methods for amblyopia treatment [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Dichoptic training is normally based on the use of polarized glasses, whereas for binocular therapy the use of red-green glasses is required. With both techniques, binocular fusion training is performed using stimuli with some common parts and disparate elements for each eye individually [17,18]. Specifically, active visual therapy based on perceptual learning, dichoptic stimulation, and binocular training with anaglyph glasses is an interesting new area of research that can complement and optimize conventional methods for amblyopia treatment [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent PEDIG study of the Dig Rush game, there was also no significant change in stereoacuity in either treatment group. 30 In the 2016 level I study of the I-BiT treatment by Herbison et al, 23 there was no significant improvement in stereoacuity among the 3 study arms (I-BiT game, I-BiT movie, sham game). In the level III study of the I-BiT by Cleary et al, 17 stereoacuity outcomes were improved.…”
Section: Binocularity and Sensory Outcomes Such As Stereopsismentioning
confidence: 96%
“…In addition, lowcontrast VA was evaluated and found to have improved in 67% of subjects. On the basis of these results, a level I randomized controlled trial was organized and reported in 2016 by Herbison et al 23 In this study, 75 children (ages 4e8 years) were randomized to an active I-BiT game (n ¼ 26), an I-BiT movie (n ¼ 24), or a sham game (n ¼ 25). Treatment consisted of 30-minute weekly sessions over 6 weeks.…”
Section: Amblyopic Eye Visual Acuitymentioning
confidence: 99%
“…El enfoque binocular pretende obtener, a través de la estimulación de ambos ojos, un efecto secundario sobre la agudeza visual, al eliminar la supresión interocular y permitir la fusión (41). Hess y Thompson describen una serie de tratamientos que permiten la participación del ojo dominante en la terapia (41); es el caso de un tratamiento interactivo binocular (figura 2), también llamado iBit System (42)(43)(44). Otra propuesta es el protocolo de aprendizaje perceptual denominado Push-Pull (45) y un enfoque de juego de acción creado por Noah (46).…”
Section: Tratamientounclassified